2018
DOI: 10.1002/cssc.201800625
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Crystallization by Methanol Additive in Antisolvent for Achieving High‐Quality MAPbI3 Perovskite Films in Humid Atmosphere

Abstract: Perovskite solar cells have attracted considerable attention owing to their easy and low-cost solution manufacturing process with high power conversion efficiency. However, the fabrication process is usually performed inside a glovebox to avoid moisture, as organometallic halide perovskites are easily dissolved in water. In this study, we propose a one-step fabrication of high-quality MAPbI perovskite films in around 50 % relative humidity (RH) humid ambient air by using diethyl ether as an antisolvent and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 45 publications
5
43
0
Order By: Relevance
“…As it is known that lower Rs suggests a better electro transport and larger R rec implies the lower recombination rate. According to Figure S10, the solar cell device based on CsPb 0.8 Ge 0.2 I 2 Br has a much higher R rec than that of CsPbI 2 Br which determined from the width of the semicircle, suggesting the recombination rate is decreased by Ge incorporation . Therefore, it can be concluded that the larger R rec of Ge incorporated perovskite device indicates that the carrier mobility in correspondent device is improved thus leading to enhanced V oc and FF.…”
Section: Figurementioning
confidence: 95%
“…As it is known that lower Rs suggests a better electro transport and larger R rec implies the lower recombination rate. According to Figure S10, the solar cell device based on CsPb 0.8 Ge 0.2 I 2 Br has a much higher R rec than that of CsPbI 2 Br which determined from the width of the semicircle, suggesting the recombination rate is decreased by Ge incorporation . Therefore, it can be concluded that the larger R rec of Ge incorporated perovskite device indicates that the carrier mobility in correspondent device is improved thus leading to enhanced V oc and FF.…”
Section: Figurementioning
confidence: 95%
“…[21] Their sophisticated setup consisted in an atmospheric box of controllable RH, where dry N 2 was used as the carrier gas, flowing through a set of water bubblers into the atmospheric bag (Figure 4a). [51] In their work, methanol is used as an additive onto the diethylether antisolvent to remove the residual water occluded in the perovskite material during first steps of crystallization (Figure 4b). [50] More recently, an interesting additive-antisolvent method under room conditions has been proposed by Yang et.al.…”
Section: Effect Of H 2 O As Moisture In Ambient Atmospherementioning
confidence: 99%
“…[50] More recently, an interesting additive-antisolvent method under room conditions has been proposed by Yang et.al. [51] In their work, methanol is used as an additive onto the diethylether antisolvent to remove the residual water occluded in the perovskite material during first steps of crystallization ( Figure 4b). They proposed an enhanced crystallinity lacking of pinholes and reduced hysteretic behaviour in devices prepared with their method, attributing this effect to a fast extraction of water molecules during the annealing step, as methanol has high water solubility.…”
Section: Effect Of H 2 O As Moisture In Ambient Atmospherementioning
confidence: 99%
“…A wide number of methods have been developed to detect and quantify the ionic diffusion rates. Photothermal induced resonance (PTIR), kelvin probe force microscopy (KPFM), 207 Pb NMR, 127 I NMR/NQR, tracer diffusion, reaction cell, doping experiments, galvanostatic measurement, impedance spectroscopy (IS) or suppression of luminescence in laterally contacted electrodes, are some of the main responsible techniques which provides evidences of ionic migration and specific values of their diffusion coefficients (Table 1). 79,80,81 A recent review published by Wang et.al.…”
Section: 512ion Migrationmentioning
confidence: 99%
“…al. 127,128 In their work, methanol is used as an additive onto the diethylether antisolvent to remove the residual water occluded in the perovskite material during first steps of crystallization ( Fig.1.33b). They proposed an enhanced crystallinity lacking of pinholes and reduced hysteretic behaviour in devices prepared with their method, attributing this effect to a fast extraction of water molecules during the annealing step, as methanol has high water solubility.…”
Section: 524effects Of Water Exposure To Films/devicesmentioning
confidence: 99%